Deep liquid neural network for prediction of weather-impacted flight delay - Bisandu, Desmond B.; Chandrakumar, Majuran; Moulitsas, Irene (Elsevier, 2026)
In this paper, we developed and analysed a model for predicting flight delays, focusing on those caused by weather conditions. Flight delays pose a significant problem for airlines, as the growth of air traffic often results in financial losses and passenger inconvenience. Unlike several previous research papers, this study provides a more detailed analysis of delays, distinguishing between weather-related and non-weather-related delays. Deep Learning (DL) models, including the proposed Liquid Neural Networks (LNN), Long Short-Term Memory (LSTM), and Multi-Layer Perceptron (MLP), were utilised to make predictions. We compare the LNN model, which has not been used previously for flight delay prediction, with the other two DL models. For this research, we employed two reliable datasets: flight data from the Bureau of Transportation Statistics and weather data from the Weather Underground site. Our methodological approach is comprehensive in addressing challenges encountered with the data. One major challenge was managing class imbalance, which can affect prediction accuracy, using the Synthetic Minority Over-sampling Technique algorithm. The selection of features for training and evaluation was based on mutual information scores and Pearson correlation coefficients. Hyperparameter optimisation was carried out systematically using grid search and trial-and-error. Models were evaluated with standard performance metrics, including precision, recall, F1-score, accuracy, and a confusion matrix. The results reveal that the LNN model outperformed the other DL models in predicting flight delays, particularly for the two classes related to delay occurrence. Overall, all three models produced excellent results in predicting on-time flights and acceptable outcomes when forecasting delays due to non-weather factors. However, the LNN model exhibited computational limitations when predicting weather-related delays, with notably lower scores for this class and significantly longer training durations. Despite these limitations, the LNN model demonstrated promising performance compared to prior models, even surpassing them on some metrics. These findings indicate that the LNN model has great potential for future flight delay prediction.
Keywords: 46 Information and Computing Sciences; 40 Engineering; 4611 Machine Learning; 35 Commerce, Management, Tourism and Services; Basic Behavioral and Social Science; Bioengineering; Machine Learning and Artificial Intelligence; Networking and Information Technology R&D (NITRD); Behavioral and Social Science; Flight delay prediction; Deep learning; Liquid neural networks; Long short-term memory; Multi-layer perceptron; Class imbalance; SMOTE